PENERAPAN PRINSIP EKOWISATA PADA TAMAN HUTAN RAYA SULTAN SYARIF HASYIM DI PROVINSI RIAU - Yanti, Lola Feby; Yusrizal, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The great forest park of sultan sharif hashim in riau has the potential of ecotourism. Ecotourism principles such as preserving biodiversity, participation of local communities, environmental education, and economic benefits to communities are discussed in this study. A qualitative study is conducted with interviews, observation, and document analysis. The results showed that despite the challenges, the principle of ecotourism has been applied. Community participation continues through training and empowerment, while conservation efforts such as reforestation and habitat maintenance are well underway. Various activities are also used to carry out ward education programs. The increased local incomes involved demonstrate positive economic effects. As a result, the principle of ecotourism in tahura sultan sharif hashim can help with the conservation and welfare of the community, provided that problems are overcome through continued cooperation Keywords: Environmental Conservation, Local Community Participation, Economic Benefits, Tourism Management